THE POSITIVE IMPACT OF BORROWINGS IN THE DEVELOPMENT OF ENGLISH VOCABULARY - Jumanova Go`zal Alisherovna (PEDAGOGS, 2025)
Abstract: The lexical richness of the English language is complemented by a large number of words borrowed from other languages during its historical development. Incoming words have played an important role in expanding the pronunciation, writing and meaning of English, making it the most global language in the world. This article analyzes how words that are part of the development of the English language have a positive effect.